Axl inhibition: a potential road to a novel acute myeloid leukemia therapy?. Issue 2 (April 2015) - Janning, Melanie; Ben-Batalla, Isabel; Loges, Sonja
<x xml:space="preserve">Abstract</x> Novel treatment options in acute myeloid leukemia (AML) are urgently needed; treatment has not changed significantly over the past decades and survival is still dismal, especially in elderly patients. Axl, a member of the Tyro3, Axl, Mer (TAM) receptor family, mediates proliferation and survival of AML cells and is upregulated upon cytostatic treatment. In addition, AML cells induce expression of the Axl ligand growth arrest-specific gene 6 (Gas6) in bone marrow stroma cells, which further amplifies their growth and therapy resistance. Interruption of Axl signaling by pharmacological approaches, including the small molecule Axl inhibitor BGB324, decreased disease burden and prolonged survival of AML mice. The Gas6-Axl pathway has translational relevance because Axl is expressed by approximately 50% of AML patients and Axl-targeting approaches can block growth of primary human AML cells. Thus, Axl represents a potential novel target in AML and BGB324 is now in clinical development.